AKULTURASI BUDAYA DALAM PUJAWALI DI PURA BENCINGAH, DESA AMBENGAN KECAMATAN SUKASADA, KABUPATEN BULELENG - I Putu Mardika (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2019)
Pura Bencingah, Sukasada Sub-District, Buleleng Regency has the historical value of the struggle of the Balinese people, especially in Buleleng, established because of a vow (promise) of fighters in terms of seizing independence from invaders to the Almighty God. So that it has a very thick acculturation at the time of praising which is very interesting to study. This study aims to find out philosophical values, pujawali procession and cultural acculturation found in Pura Bencingah. In this study, problems were examined using the theory of Social Change, Religious Theory and Cultural Acculturation. The results showed that the philosophical value of the Bencingah temple was founded on the feeling of obtaining a sense of security (raksanam) from Ida Sang Hyang Widi Wasa when fighting and liberating the Indonesian nation from the shackles of colonialism, as a form of state and religion. The procession at the preliminary ceremony was held at Soma Kliwon Wuku Kuningan (Soma Macekan Agung) in Bencingah Temple led by Pura Bencingah Jro Mangku Dalem Chief witnessed directly by pemedek and veteran fighters using banten facilities such as banten for offal, banten for sekonghe gong and help caru. Cultural acculturation that can be seen in this pujawali is when the process of mepurwa daksina (walking around the main monument) while carrying a red and white flag 2 stalks of the arena followed by approximately 15 people rotating 3 times. This procession was accompanied by a bell / bajra sound by the Bencingah temple langang. At this time, the pemedek who came to pray joined in singing a great Indonesian song accompanied by the sound of Gong (gambelan "longgoran" at the time murwa daksina) and after that continued with a moment of silence. Keywords: Cultural Aculturations, Pujawali, Desa Ambengan